A feasibility study of the use of lime piles for soil stabilization - Yu, Kuen; Moh, Za-Chieh; Richardson, A.M.; Brenner, R.P.; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1975)
Twenty-eight undisturbed soil samples were taken from the campus of Asian Institute of Technology at Rangsit at the depth from 1.5 m to 4.5 m below the existing ground surface. Quicklime piles or hydrated lime piles were placed in the center of the soil samples and extended to the entire depth. Two sizes of lime pile, 2 cm and 3 cm diameter were used in the study with lime (CaO) content varied from 3 to 7%. The lime pile treated soil samples were cured for 1, 3, 4, 6 and 12 weeks under moist and ambient temperature or constant temperature conditions. Static cone penetration tests and plate bearing tests were employed to evaluate the response of soils to lime pile treatment. Both types of lime piles were effective in changing the soil characteristics, but the extent of effectiveness was limited to a distance not more than one diameter of the pile from the pile surface after 12 weeks of curing. Quicklime pile caused considerable reduction in the soil moisture content and consolidation of the soil surrounding the pile. Reactions occurred fairly rapid. Strength increase in soil around hydrated lime was primarily due to pozzolanic reaction between diffused lime and soil material.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand.
Thesis (M.Eng.) - Asian Institute of Technology,1975
Keywords: Soil stabilization; Piling (Civil engineering)